NUTRITIONAL AND MATERNAL FACTORS INFLUENCING POSTPARTUM HAEMORRHAGE IN LAMBUSSIE DISTRICT - Taabia, F. Z.; Mornah, L. N.; Michael, W. (UDS International Journal of Development, 2022)
Maternal excessive bleeding at birth continues to be a global public health challenge, particularly in poor resource settings. Postpartum haemorrhage has been linked to a high proportion of maternal deaths and disabilities at the institutional and community levels. Current data on postpartum haemorrhage is limited to institutional settings and does not consider the community experiences of mothers who suffer from postpartum haemorrhage.This cross-sectional study assessed the nutritional and other maternal risk factors associated with postpartum haemorrhage at the community level. A total of 183 mothers were systematically sampled from six sub-districts. Data was analyzed using SPSS version 22.0. Multivariate logistic and regression models were estimated to assess the association between dependent and independent variables at a confident level of 95%. The results from the study showed that the prevalence of postpartum haemorrhage was 7.1% among the mothers interviewed in the study. Age groups (p<0.001) of mothers influenced postpartum haemorrhage as experienced by some mothers during delivery, and also maternal height (p<0.001), Iron-folic acid (IFA) daily supplements (p<0.020), Gravidity (p<0.001), anaemia (p<0.001) and malnutrition at 36 weeks of pregnancy (p<0.008). Although the prevalence of postpartum haemorrhage is relatively minor, the effects of poor nutrition on excessive maternal bleeding cannot be underestimated. Improving maternal nutritional status could reduce the chances of bleeding during delivery and possibly improve all birth outcomes. Policymakers need to develop nutrition-specific interventions for mothers before and during pregnancy.Keywords: Postpartum, Haemorrhage, Maternal, Nutrition, Risk-Factors